PELATIHAN RENANG GAYA DADA 8 KALI 25 METER 4 SET LEBIH MENINGKATKAN KECEPATAN RENANG 100 METER GAYA DADA DARIPADA 4 KALI 50 METER 4 SET PADA RENANG PEMULA PUTRA - Suarta, I Wayan (Sport and Fitness Journal; volume 1, no 1, 2013)
Sports pool in Indonesia are well known to the public, which is reduced when driving (after the end of the recovery to begin hand pull another hand), the breaststroke is the style of the most interesting because it does not quickly tiring when compared with other styles, because the process of respiration take place with ease, making them easier use in long-distance swim, at the start to affect the pace to continue this next movement needs to get training and a variety of training models, especially at students aged 10-12 years. Training pool 8 times 25 times 50 meters and 4 meters is one of the training methods that can speed up travel time. The best training model has not been encountered in the data. So do the research to find a model training 25 meter pool 8 times and 4 times 4 sets of 50 meters. The study was conducted with pretest-postes group design. Samples taken from the novice swimmer Toya Ening on Dalung Badung, as many as 26 people were randomly selected simple. Samples were divided into 2 groups each group totaled 13 people. Both groups were equally give training in the first group to pool 8 by 25 feet 4 sets, and 4 times the second group of 4 sets of 50 meters. 0.05 ab. Differences in results were analyzed statistically with  The data analyzed were age, height, weight, leg length and physical fitness.  13.49 seconds.± 107.69, and 126.38 ±The mean test results of the final 100 meter breaststroke swimming in a row 12.14 seconds  F count the results obtained respectively by 0.95 seconds with p = 0.59 and 0.93 seconds with a value of p = 0.34. Data showed significant differences significant (p> 0.05). These results indicate that the training of swimming the breaststroke 8 by 25 feet 4 sets is better than 4 times in 4 sets of 50 meter speed up travel time 100-meter breaststroke swimming novice men (p <0.05). Suggested the use of breaststroke swimming training method 8 by 25 feet 4 sets to be intensified to provide training pool at 100 meters breaststroke to speed up travel time.
Keywords: training, swimming, up travel time